Optimalisasi Pemadanan NIK sebagai NPWP: Salah Satu Strategi Ampuh untuk Meningkatkan Penerimaan Pajak Negara? - Nur Jannah, Fiha; Anggraini Aripratiwi, Ratna (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
Tax revenues have a large portion, making tax revenue targets an important indicator of national development. The government has implemented regulations on the integration of NIK into NPWP with a Single Identity Number (SIN) system to increase taxpayer compliance as regulated in Minister of Finance Regulation Number 112/PMK.03/2022. If taxpayer compliance is higher, it will have a positive effect on tax revenue. This research uses qualitative methods, using literature studies. This research also uses secondary data, namely data taken from the websites of the Ministry of Finance and the Central Statistics Agency. Apart from that, it also examines several previous studies. The results show that there was a significant increase, reaching 23.9%, in state revenue receipts through taxes after the government regulations regarding matching NIK with NPWP. State revenues through taxes also tend to continue to increase compared to other revenues. This shows that this policy is effective in strengthening state tax revenues.